Checklists of nematodes of freshwater and marine fishes of Basrah Province, Iraq - Ali, A.H.; Mhaisen, F.T.; Khamees, N.R. (Mesopotamian Journal of Marine Sciences, 2022)
Reviewing the literature on all the nematodes parasitizing 45 species of freshwater and marine fishes of Basrah province (eight elasmobranchs and 37 teleosts) indicated the presence of 48 nematode taxa. Thirty-five of such nematodes were recorded from marine localities against eight taxa from freshwater localities and two taxa from both marine and freshwater localities. These nematodes belong to two classes, three orders and eight families. All such nematodes belong to the class Secernentea except two taxa which belong to the class Adenophorea. Orders Ascaridida and Spirurida are represented with 22 and 24 taxa, respectively, while order Enoplida has only two taxa. The total number of nematode species recorded for each fish host species fluctuated from a minimum of one nematode species in 17 fish hosts to a maximum of eight nematode taxa in Cynoglossus arel only. Number of fish hosts reported for these nematodes fluctuated from one host in case of 31 taxa to a maximum of 20 hosts in case of Contracaecum sp. 1 larva.